The association between neostigmine and postoperative atelectasis in elderly patients undergoing laparoscopic pancreaticoduodenectomy: a retrospective single-center propensity score matched study - Rong Luo; Yunfen Ge; Yue Chen; Huizi Liu (BMC Anesthesiology)
Abstract Background It is uncertain whether neostigmine reversal improves postoperative pulmonary outcomes. This study aimed to evaluate the association between neostigmine and postoperative atelectasis, and other complications in elderly patients undergoing laparoscopic pancreaticoduodenectomy (LPD). Methods This single-center retrospective cohort study included elderly patients who underwent LPD between 2019 and 2022, using cis-atracurium as the sole neuromuscular blocking agent. Participants were divided into two groups based on exposure to neostigmine: the neostigmine reversal group (exposed) and the control group (not exposed). The primary endpoint was the incidence of atelectasis within the first 3 postoperative days. Secondary endpoints included the incidence of pneumonia, pleural effusion, acute respiratory distress syndrome (ARDS), time to extubation, length of stay in the post-anesthesia care unit (PACU) and hospital, reintubation, postoperative blood gas analysis, 30-day readmission, and 30-day mortality. Propensity score matching (PSM) was performed based on baseline and intraoperative characteristics to minimize potential bias. Results Of the 501 patients initially included, 302 were successfully matched after PSM at a 1:5 ratio, comprising 89 patients in the neostigmine reversal group and 213 in the control group. Compared to the control group, the incidence of postoperative atelectasis was lower in the neostigmine reversal group (OR 0.43 [95% CI 0.24–0.75], p = 0.003) in elderly patients undergoing elective LPD. For secondary outcomes, time to extubation (Median [IQR] 20.00 [10.00-32.50] min vs. 25.00 [15.00–41.00] min, p < 0.001), and the length of stay in the PACU (Median [IQR] 55.00 [45.00-67.50] min vs. 60.00 [50.00–84.00] min, p = 0.013) were shortened, and the oxygen index (OI) at 2 h after extubation was increased (Median [IQR] 339.00 (275.76-453.03) vs. 310.00 (262.31–378.00), p < 0.001) in the neostigmine reversal group. Binomial logistic regression showed that age (OR 1.08 [95% CI 1.04–1.12], p < 0.001), neostigmine reversal (OR 0.43 [95% CI 0.24–0.76], p = 0.004), and intraoperative total fluid infusion (OR1.00 [95% CI 1.000-1.001], p = 0.009) were significantly associated with atelectasis after LPD. Conclusions In this single-center PSM study, neostigmine reversal was associated with lower incidence of atelectasis within the first 3 postoperative days, shorter time to extubation, shorter length of stay in the PACU, and increased OI at 2 h after extubation in elderly patients undergoing elective LPD. Postoperative atelectasis was associated with older age, greater intraoperative total fluid infusion, and the absence of neostigmine reversal. These results should be interpreted as hypothesis-generating, and warrant validation through randomized controlled trials.